Analisis Biaya Produksi Kerajinan Rotan pada Industri Usaha Kecil dan Menengah (UKM) di Kecamatan Kuala Kabupaten Nagan Raya - Wati, Nova; Ertika, Yenni; Sani, Sri Rosmiati (Universitas Teuku Umar, 2024)
UD. Karya Rotan is a small and medium enterprise (UKM) industry located in Ujong Rambong Village in Kuala District, Nagan Raya Regency, which is engaged in processing rattan into furniture in Kuala District. Production costs are an important factor to consider when U.D Karya Rotan will produce rattan. The purpose of this research was to determine the production costs of rattan handicrafts in the small and medium enterprise industry at UD. Karya Rotan in Kuala District, Nagan Raya Regency. The results showed that the total production costs for making rattan crafts by UD Karya Rotan from January to December 2022 amounted to Rp. 4,806,278 with an average of Rp. 2,140,030 per month where the maximum cost was Rp. 3,450,333 spent on making 42 units of bulkhead crafts and a minimum cost of IDR 1,071,458 was spent on making 53 units of handsome crafts.